Students' Multirepresentation Ability in Completing Physics Evaluation Problems - Rambu Ririnsia Harra Hau; Paulina Nelce Mole; Agustina Elizabeth; Yohanes Sudarmo Dua; Maria Yani Leonarda (STKIP Singkawang, 2020)
This study aims to describe students' multi-representation ability in solving physics evaluation questions carried out by the qualitative description method in class X MIA 1 SMA Katolik St. Gabriel Maumere for the 2019/2020 school year. The data were obtained from the matter of physics evaluation on Newton's law material about the force of gravity. Data analysis is based on student work steps in solving evaluation questions. Data analysis results show that the ability of multi-representation in solving physics problems on Newton's law material about the force of gravity in the high category. The number of mathematical representations of 100%, image representation of 10%, then in the medium type only uses a mathematical description of 100% and in the low category using a mathematical representation of 100% and a verbal representation of 40%.